1956
DOI: 10.1172/jci103337
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Estimation of Epinephrine and Norepinephrine in Human and Canine Plasma. I. A Critique of the Ethylenediamine Condensation Method 1

Abstract: The recovery of epinephrine (E) and norepinephrine (N) from plasma on activated alumina is reproducible and this adsorption technique can be made reasonably specific for catechols. The development of chemical methods for the assay of E and N in peripheral plasma has been hampered, however, by: 1) the low concentrations of E and N normally present (1 ,jg. per L.-or less); 2) the lack of specificity of the methods for E and N in the presence of other catechols which are excreted in urine (1, 2) and thus presumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1958
1958
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…More recently Born & Hornykiewicz (1957) Table 1 suggests that where great care is taken to maintain the platelets and the integrity of the plasma generally (Valk & Price, 1956), the adrenaline and noradrenaline values are at their lowest. Where maximum disruption of platelets is likely to occur, as in the fluoride solution, maximum catecholamine values are found.…”
Section: Discussionmentioning
confidence: 99%
“…More recently Born & Hornykiewicz (1957) Table 1 suggests that where great care is taken to maintain the platelets and the integrity of the plasma generally (Valk & Price, 1956), the adrenaline and noradrenaline values are at their lowest. Where maximum disruption of platelets is likely to occur, as in the fluoride solution, maximum catecholamine values are found.…”
Section: Discussionmentioning
confidence: 99%
“…The question arises whether the catechol amines which are found in blood (Holzbauer and Vogt, 1954) are likewise concentrated in the platelets. Results obtained with human blood by WeilMalherbe and Bone (1954) and by Robinson and Stott (1958) suggested that this was so, although Valk and Price (1956) found no catechol amines in human platelets.…”
mentioning
confidence: 94%
“…In this respect, the EDA method is inferior to the THI method (6,8,9), a fact which is emphasized by the false high readings of the former in uremia (10). However, the THI method may measure dopamine (3, 4), dihydroxyphenylalanine (2-4), isopropylnorepinephrine (2-4, 9), serotonin (2) or aureomycin (11) modification used.…”
mentioning
confidence: 99%
“…In this respect, the EDA method is inferior to the THI method (6,8,9), a fact which is emphasized by the false high readings of the former in uremia (10). However, the THI method may measure dopamine (3,4), dihydroxyphenylalanine (2)(3)(4), isopropylnorepinephrine (2-4, 9), serotonin (2) or aureomycin (11), depending on the * This investigation was supported (in part) by a grant from the Life Insurance Medical Research Fund, and by a research grant (H-4807) and a training grant (HTS-5369) from the National Heart Institute, Bethesda, Md. modification used.…”
mentioning
confidence: 99%